Combined Technique of Temporal Muscle Augmentation for Muscle Reconstruction in Case of Small to Medium Anatomic Defects. Issue 7 (October 2020) - Gagliardi, Filippo; Roncelli, Francesca; Noris, Alice; Piloni, Martina; Bailo, Michele; Caputy, Anthony J.; Mortini, Pietro
Abstract : Abstract: Inadequate temporal muscle (TM) reconstruction after surgery may hesitate in potentially severe functional and aesthetic sequelae, making it of paramount importance to carefully consider TM reconstruction even in case of small deformities. The authors describe the combined temporal muscle augmentation technique (CTMA), an innovative technique for TM augmentation for muscle reconstruction in case of small to medium substance loss. A cadaver study was conducted as preclinical validation of the technique for the assessment of CTMA coverage capability. CTMA consists in a combination of 2 techniques for muscle surface coverage (MSC) increase: the radial (RA) and the longitudinal augmentation (LA), which enables to harvest a radial (RF) and a longitudinal flap (LF), respectively. Each flap derives from a different muscle-bundle, spearing TM segmentation and functional performance, and are supplied by a specific neuro-vascular peduncle, which makes flaps functionally independent. A surgical case is reported to demonstrate the feasibility of the technique. Combined temporal muscle augmentation technique provides an overall coverage surface of 6.5 ± 0.6 cm 2, which corresponds to a gap distance of 2.5 ± 0.2 cm, with RF providing a statistically significant larger surface of coverage compared to LF (×2.1; P  = 0.0001). Combined temporal muscle augmentation technique is easy and fast to perform displaying a good reconstructive capability with complete preservation of temporal muscle anatomic compartmentalization and segmental vasculature. It might be considered as a safe and effective alternative in the reconstruction of small-to medium TM defects. Abstract : Supplemental Digital Content is available in the text